The Restoring Ecological Health to Your Land Workbook - Apfelbaum, Steven I.; Haney, Alan.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2012)
The Restoring Ecological Health to Your Land Workbook is the first practical guidebook to give restorationists and would-be restorationists with little or no scientific training or background the “how to” information and knowledge they need to plan and implement ecological restoration activities. The book sets forth a step-by-step process for developing, implementing, monitoring, and refining on-the-ground restoration projects that is applicable to a wide range of landscapes and ecosystems.   The first part of the book introduces the process of ecological restoration in simple, easily understood language through specific examples drawn from the authors’ experience restoring their own lands in southern and central Wisconsin. It offers systematic, step-by-step strategies along with inspiration and benchmark experiences. The book’s second half shows how that same “thinking” and “doing” can be applied to North America’s major ecosystems and landscapes in any condition or scale.   No other ecological restoration book leads by example and first-hand experience like this one. The authors encourage readers to champion restoration of ecosystems close to where they live . . . at home, on farms and ranches, in parks and preserves. It provides an essential bridge for people from all walks of life and all levels of experience—from land trust member property stewards to agency personnel responsible for restoring lands in their care—and represents a unique and important contribution to the literature on restoration.
Preface -- Introduction -- Step 1. Inventory and Map Your Land. Task 1. Create a Basemap. Task 2. Characterize Land Use or Cover Types. Task 3. Refine Ecological Units. Task 4. Map Current Conditions of Ecological Units. Task 5. Review Soil Type Distributions and Assess Seedbanks. Task 6. Map Drainage. Task 7. Map Locations of Significant Populations of Invasive Species. Task 8. Assess and Map Stressors -- Step 2. Investigate Historic Conditions. Task 9. Complete Historic Conditions Data Form. Task 10. Map Soils and Surface Geology. Task 11. Understand How Your Land Has Changed -- Step 3. Interpret Landscape Changes. Task 12. Develop Working Hypotheses. Task 13. Map Ecotones and Gradients -- Step 4 Develop Goals and Objectives. Task 14. Develop Restoration Goals and Objectives. Task 15. Review and Firm Up Framing Infrastructure. Task 16. Develop a Project Governance Plan. Task 17. Prepare a Preliminary Budget. Task 18. Refine Goals and Objectives -- Step 5. Develop Your Restoration Plan. Task 19. Design the Outline (Content) of Your Plan -- Step 6. Develop a Good Monitoring Program. Task 20. Develop Your Monitoring Program -- Step 7. Implement the Plan. Task 21. Develop a Task List and Schedule. Task 22. Develop Project Phasing Plans. Task 23. Develop Detailed Specifications. Task 24. Determine Restoration Methods and Equipment Needs. Task 25. Procure Plants, Seeds, and Materials. Task 26. Complete Final Budget. Task 27. Develop Long-term Maintenance Budget and Endowment -- Step 8. Maintain Good Records. Task 28. Decide What Will Be Recorded. Task 29. Develop a Record-keeping Strategy -- Step 9. Review the Project. Task 30. Schedule Semiannual and Annual Reviews. Task 31. Refine the Restoration Program as Suggested by the Review -- Step 10. Share the Restoration Process. Task 32. Develop a Plan for Sharing Your Experiences -- appendix 1. data forms -- appendix 2. equipment, safety, and protection for restoration planning -- appendix 3. restoration contracts -- appendix 4. additional resources for readers.
Keywords: Environmental management; Ecosystems; Landscape ecology; Conservation biology; Ecology .; Nature conservation; Environmental Management; Ecosystems; Landscape Ecology; Conservation Biology/Ecology.; Nature Conservation